Hypermethylation: Causes and Consequences in Skeletal Muscle Myopathy. Issue 8 (21st April 2017) - Majumder, Avisek; Behera, Jyotirmaya; Jeremic, Nevena; Tyagi, Suresh C.
ABSTRACT: A detrimental consequence of hypermethylation is hyperhomocysteinemia (HHcy), that causes oxidative stress, inflammation, and matrix degradation, which leads to multi‐pathology in different organs. Although, it is well known that hypermethylation leads to overall gene silencing and hypomethylation leads to overall gene activation, the role of such process in skeletal muscle dysfunction during HHcy condition is unclear. In this study, we emphasized the multiple mechanisms including epigenetic alteration by which HHcy causes skeletal muscle myopathy. This review also highlights possible role of methylation, histone modification, and RNA interference in skeletal muscle dysfunction during HHcy condition and potential therapeutic molecules, putative challenges, and methodologies to deal with HHcy mediated skeletal muscle dysfunction. We also highlighted that B vitamins (mainly B12 and B6), with folic acid supplementation, could be useful as an adjuvant therapy to reverse these consequences associated with this HHcy conditions in skeletal muscle. However, we would recommend to further study involving long‐term trials could help to assess efficacy of the use of these therapeutic agents. J. Cell. Biochem. 118: 2108–2117, 2017. © 2017 Wiley Periodicals, Inc. Abstract : A detrimental consequence of hypermethylation is hyperhomocysteinemia (HHcy), that causes oxidative stress, inflammation, and matrix degradation, which leads skeletal muscle myopathy.